Determination of zinc, copper, selenium, and manganese in human milk using acid digestion by ICP-MS and its application in biological trace element monitoring - Mohd Taufek, Nor Hidayah; Mohmad Sabere, Awis Sukarni; Mohamad Jamahari, Ummi Syahidah; Amran, Nur Balkhis; Fata Nahas, Abdul Rahman; Bidai, Joseph (IIUM Press, 2023)
Introduction: Human milk contains essential trace elements which support healthy development of infants. Previous studies have reported various analytical methods using different instruments to measure trace elements in human milk. This study aimed to determine trace element concentration in human milk using a validated acid digestion method and its application in biomonitoring among postpartum mothers. Method: Human milk samples were collected from three postpartum mothers and prepared using acid digestion method. All samples were analysed using inductively coupled plasma mass spectrometry (ICP-MS) and all validation parameters were measured. Results: Four trace elements which were zinc, copper, manganese and selenium were found to have good linearity (r² > 0.99), limit of detection in μg/L (0.06, 0.0001, 0.005, 0.00003, respectively) and limit of quantification in μg/L (0.18,0.0003, 0.02, 0.0001, respectively). Good accuracy (83.4 – 112.7%), inter-day, and intra-day repeatability were obtained. Method application on trace element monitoring over postpartum period of three participants showed the median concentration of zinc, copper and selenium in human milk gradually decreased with slight variation, whereas manganese remained stable. Positive significant correlations were observed for most of the elements (r > 0.40, p < 0.001) except for copper-manganese. Conclusion: Acid digestion method is sensitive, accurate and precise to analyse and quantify zinc, copper, manganese and selenium concentrations in human milk simultaneously by ICP-MS. It can be applied to monitor trace elements concentration in human milk in clinical and public health settings.